2016
DOI: 10.1016/j.ypmed.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity on schoolchildren's academic performance: The Active Smarter Kids (ASK) cluster-randomized controlled trial

Abstract: This large, rigorously conducted cluster RCT in 10-year-old children supports the notion that there is still inadequate evidence to conclude that increased physical activity in school enhances academic achievement in all children. Still, combining physical activity and learning seems a viable model to stimulate learning in those academically weakest schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
191
2
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(233 citation statements)
references
References 25 publications
6
191
2
24
Order By: Relevance
“…Higher MVPA was related to higher academic achievement in writing and numeracy but not in reading and spelling 31. In an intervention study, there was a significant effect of physical activity on numeracy among the children who initially performed the most poorly on the test, but no significant effect of the intervention on academic achievement measures was observed using intention-to-treat analyses 35. These studies that partially supported a positive relationship between objectively measured physical activity and academic achievement were performed in different countries, with sample sizes ranging from 232 to 4755 children and adolescents.…”
Section: Resultsmentioning
confidence: 85%
“…Higher MVPA was related to higher academic achievement in writing and numeracy but not in reading and spelling 31. In an intervention study, there was a significant effect of physical activity on numeracy among the children who initially performed the most poorly on the test, but no significant effect of the intervention on academic achievement measures was observed using intention-to-treat analyses 35. These studies that partially supported a positive relationship between objectively measured physical activity and academic achievement were performed in different countries, with sample sizes ranging from 232 to 4755 children and adolescents.…”
Section: Resultsmentioning
confidence: 85%
“…Chaya and colleagues36 compared daily yoga with structured PA (stretching and aerobic exercise) and found no significant differences on any of the cognitive performance tests between groups. Resaland et al 83 found no significant intervention effect on mathematics, reading or English in 10-year-old children. Analyses of the subgroup who performed worse at baseline for numeracy showed significant beneficial effects of the intervention.…”
Section: Resultsmentioning
confidence: 95%
“…Valid data were provided from 1,129 children (Supplemental Figure 1). As there were no differences in physical activity levels (Resaland et al, 2016), aerobic fitness, and motor skills (Aadland et al, in press) between children in the intervention- and control group during the trial, both groups were included in the present study. We only provide a brief overview of relevant methods below as a detailed description of the study is given elsewhere (Resaland et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A recent intervention study by Mullender-Wijnsma et al (2016) found improved performance in mathematics and spelling after 2 years of physically active mathematics and language lessons. However, neither the 5-month Learning, Cognition, and motion (LCoMotion) trial (Tarp et al, 2016), nor the 7-month ASK trial (Resaland et al, 2016), found evidence for an effect of physical activity interventions on academic performance.…”
Section: Introductionmentioning
confidence: 99%